2022
DOI: 10.3390/ijms23169428
|View full text |Cite
|
Sign up to set email alerts
|

Over-Expression of an R2R3 MYB Gene, MdMYB108L, Enhances Tolerance to Salt Stress in Transgenic Plants

Abstract: Plants are affected by various abiotic stresses during their growth and development. In plants, MYB transcription factors are involved in various physiological and biochemical processes, including biotic and abiotic stress responses. In this study, we functionally analyzed MdMYB108L. We examined the transcriptional activity of MdMYB108L under salt stress and determined that the N-terminal domain of MdMYB108L, which was significantly induced under salt stress, has transcriptional activity. MdMYB108L overexpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Many reports have described that MYB TFs are involved in response to abiotic stress in different plants (Ambawat et al, 2013; Jung et al, 2008; Zhang et al, 2011). In several works, different MYB TFs were up‐regulated by stress conditions and different approaches have demonstrated the role of MYB genes in response to abiotic stress (An et al, 2018; Du et al, 2022; Wang et al, 2021; Yang et al, 2012; Zhou et al, 2022). Nevertheless, there are no works describing a possible role of the MYB36 gene in response to stress conditions in plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reports have described that MYB TFs are involved in response to abiotic stress in different plants (Ambawat et al, 2013; Jung et al, 2008; Zhang et al, 2011). In several works, different MYB TFs were up‐regulated by stress conditions and different approaches have demonstrated the role of MYB genes in response to abiotic stress (An et al, 2018; Du et al, 2022; Wang et al, 2021; Yang et al, 2012; Zhou et al, 2022). Nevertheless, there are no works describing a possible role of the MYB36 gene in response to stress conditions in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Many reports have described that MYB TFs are involved in response to abiotic stress in different plants (Ambawat et al, 2013;Jung et al, 2008;Zhang et al, 2011). In several works, different MYB TFs were up-regulated by stress conditions and different approaches have demonstrated the role of MYB genes in response to abiotic stress (An et al, 2018;Du et al, 2022;Wang et al, 2021;Yang et al, 2012;Zhou et al, 2022) have reported chlorophyll-deficient soybean plants with a concomitant reduction in isoflavone levels (Mikuriya et al, 2017;Shiroshita et al, 2021). Also interestingly, a recent work in cucumber has reported that Csmyb36 mutants have also lower chlorophyll content concluding that CsMYB36 may regulate the yellow-green coloration in cucumber by interacting and/or changing the expression levels of a pigment protein gene and other genes (Hao et al, 2018).…”
Section: Ljmyb36 Mutants Show Higher Sensitivity To Salt Light and Th...mentioning
confidence: 99%
“…The soluble sugar content (mg/g) and proline content (µg/g) were measured using the anthrone method [26] and the ninhydrin method [27], respectively. To measure the soluble sugar content, 0.5 g fresh leaves tissue was boil water bathed for 20 min with 15 mL distilled water.…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…The peroxidase (POD) activity (U/g) was measured with the guaiacol method [27]. To obtain the enzyme solution, 1 g of fresh leaves tissue was ground with 5 mL 0.1 mol•L −1 phosphate buffer solution (pH = 6).…”
Section: Biochemical Analysesmentioning
confidence: 99%
“…The 2R-MYB genes, named R2R3-MYB, were usually the largest MYB gene subfamily in green plants ( Martin and Paz-Ares, 1997 ). They play essential roles in plant lifetime, including (1) primary and secondary metabolites, such as phenylpropanoid metabolism ( Liu et al., 2015 ; Tang et al., 2021 ), flavonoid biosynthesis ( Czemmel et al., 2012 ; Lin et al., 2021 ; Zhao et al., 2022b ), anthocyanin biosynthesis ( Naing and Kim, 2018 ; Upadhyaya et al., 2021 ; Wang et al., 2022c ), chlorogenic acid biosynthesis ( Tang et al., 2021 ), indolic and aliphatic glucosinolate biosynthesis ( Gigolashvili et al., 2009 ), and apigenin biosynthesis ( Wang et al., 2022b ); (2) cell fate and identity, for instance, epidermis and root formation ( Du et al., 2009 ); (3) developmental processes, like embryogenesis ( Wang et al., 2009 ), pollen development ( Liu et al., 2021 ), male sterility ( Yu et al., 2021 ), and plant trichome development ( Shangguan et al., 2021 ); and (4) responses to biotic and abiotic stresses, including diseases ( Shen et al., 2017 ; Gu et al., 2020 ; Hawku et al., 2022 ), high salinity ( Wang et al., 2021a ; Du et al., 2022 ), cold ( Dong et al., 2021 ), heat ( Wu et al., 2021b ), and drought ( Lv et al., 2021 ; Wu et al., 2021a ).…”
Section: Introductionmentioning
confidence: 99%